Analisis Kinerja Birokrasi Pelayanan Pajak Bumi dan Bangunan Sektor Perdesaan dan Perkotaan (PBB-P2) Dalam Meningkatkan Pendapatan Asli Daerah Pada Badan Pengelolaan Pajak Dan Retribusi Daerah Kota Medan - Benny Sinomba Siregar; Isnaini Isnaini; Budi Hartono (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This study aims to determine the Bureaucratic Performance of Land and Building Tax Services in the Urban and Rural Sector (PBB-P2) in Increasing Regional Original Income at the Regional Tax and Retribution Management Agency in Medan City and to find out and analyze what factors support and inhibit it. The research method used is descriptive research with observation data collection instruments, documentation studies and interviews, while the data analysis is descriptive analysis. The results of this study indicate that the performance of the Regional Tax and Retribution Management Agency in optimizing the increase in Local Own Revenue through the receipt of Land and Building Taxes for the Urban Sector in Medan City is analyzed from the following sub-indicators: conducting socialization of Medan City Regional Regulation Number 3 of 2011 concerning Land and Building Tax for Urban and Sub-District; carry out validation activities on the Subject and Object of Land and Building Tax in the Urban and Rural Sector; carry out adjustments to the Land Value Zone (ZNT), and: carry out activities to update the Selling Value of Tax Objects (NJOP). Supporting land and building tax revenue by the Regional Revenue Agency is influenced by the following factors, namely economic growth and population. The inhibiting factors in land and building tax revenues are the awareness and compliance of taxpayers and the weakness of the tax apparatus. Meanwhile, the government's recommendation is to socialize regulations regarding local taxes, make adjustments and determine Land Value Zones (ZNT) and update the Sales Value of Tax Objects (NJOP).